Differential Impact of the Perception of Ethical Climates upon Job Satisfaction Among Different Types of Employees - Zimmerman, Glenn; Munteanu, Radu; Walker, Andress; Buresh, Donald; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2023)
The main objective of this current research study is to examine if there are any differences between cis male and cis female employees, between managers and non-managers/subordinate employees, and between full and part-time workers in terms of their perceptions of organizational ethical climate and their self-reported job satisfaction. The research collected data from 140 participants. The research study found a statistically significant predictive effect regarding perception of workplace ethical climates scores upon the self-reported job satisfaction scores across all participants regardless of gender, employment status (full-time and part-time employees), and employment level (managers/supervisors and non-managers/subordinate employees). Another key research finding is that the self-reported job satisfaction scores predicted by the variance in the perception of workplace ethical climates scores among the managers/supervisors are over double the predictive value as compared to non-managers/subordinate employees.